G6PC1 expression as a prognostic biomarker associated with metabolic reprogramming and tumor microenvironment in hepatocellular carcinoma - Tang, Xilong; Xue, Jianjin; Li, Xiao; Zhang, Jie; Zhou, Jiajia (Frontiers in Immunology, 2025)
BackgroundHepatocellular carcinoma (HCC) is the most prevalent primary liver cancer, characterized by a poor prognosis. Many HCC patients are diagnosed at an advanced stage due to the lack of reliable prognostic biomarkers. G6PC1 (Glucose‐6‐Phosphatase Catalytic Subunit 1) is abnormally expressed in various cancers, including HCC. This study aimed to investigate the biomarker potential and biological functions of G6PC1 to elucidate its impact on HCC pathogenesis.MethodsG6PC1 expression levels were assessed using TCGA and GEO datasets. Prognostic implications were explored through Kaplan-Meier survival analysis. Potential regulatory transcription factors (TFs) were identified using four prediction tools, and functional mechanisms were investigated via GO and KEGG enrichment analyses. Associations between G6PC1 and HCC metabolic reprogramming, as well as the tumor microenvironment were analyzed.ResultsG6PC1 exhibited low expression levels in HCC, which correlated with poor patient prognosis. HNF4A may act as a regulatory factor for G6PC1 in HCC. Functional analysis identified co-expressed genes associated with metabolism-related pathways. Furthermore, G6PC1 was implicated in metabolic reprogramming, immune infiltration, and immunotherapy response.ConclusionLow G6PC1 expression, associated with poor HCC prognosis, is a potential prognostic biomarker. Integrated multi-omics analyses underscore its clinical significance, involvement in metabolic reprogramming, and immunomodulatory functions, providing a foundation for further investigation into its prognostic potential and mechanistic contributions in HCC.